Tree crown geometry and its performances on human thermal comfort adjustment - Jing Wang; Wei Guo; Chunlu Wang; Yanfeng Yao; Kou Kou; Deqing Xian; Yeting Zhang (Journal of Urban Management, 2021)
Trees play an important part in landscaping as well as thermal environment adjustment. This study selected a satellite city of Sichuan Province in China, Xindu, for field measurement about tree's crown characteristics on their cooling performances on five sunny summer days during August 2019. There were several parameters showing tree characteristics used, including tree canopying size (tree crown radius, TCR), tree geometry (the ratio of TCR to trunk height, R/TH), site openness (sky view factor, SVF), and leaf density (leaf area index, LAI). It was found that R/TH had the most significant thermal adjusting effects than others. The increase of R/TH by 1 can reduce physiological equivalent temperature by approximately 2.5~​êC (R2~​=~​0.8932) and 2.65~​êC (R2~​=~​0.8424) in the morning and afternoon respectively. SVF and LAI had less significant cooling effect due to the fact of dense-leaf season. This result provided good direction for future landscape design towards microclimate adjustment.
Keywords: 710; Canopies; Leaf area index; Outdoor thermal comfort; sky view factor; Tree crown radius